Measuring constitutional loyalty - Jerg Gutmann; Roee Sarel; Stefan Voigt (Public Choice, 2025)
We introduce a new concept, constitutional loyalty, which we define as the importance citizens ascribe to their government's compliance with constitutional rules. Its measurement across countries is challenging due to differences in context, history, and culture. We overcome this challenge by exploiting the COVID-19 pandemic as a setting in which societies around the world face unfamiliar and similar public health challenges, inducing governments to adopt comparable, yet legally untested policies. Based on novel data from a global online survey collected between 2021 and 2022, we show that citizens' support for COVID-19 mitigation policies declines if a court signals doubts about their constitutionality. We further demonstrate that this effect of constitutional loyalty depends on citizens' characteristics, such as their confidence in the courts and their moral convictions.
Keywords: D02; H12; I18; K40; P48; 330; Constitutional loyalty; COVID-19; Judicial power; Moral foundations; Trust in the judiciary